Temporal trends, clinical characteristics, and sociodemographic profile of post‐neonatally acquired cerebral palsy in Australia, 1973–2012: A population‐based observational study. (5th June 2022) - Waight, Emma; McIntyre, Sarah; Woolfenden, Susan; Watson, Linda; Reid, Susan; Scott, Heather; Martin, Tanya; Webb, Annabel; Badawi, Nadia; Smithers‐Sheedy, Hayley; ,
Abstract: Aim: To describe post‐neonatally acquired (PNN) cerebral palsy (CP) in terms of temporal trends in prevalence, clinical and sociodemographic profiles, known causes and associations between causes, and sociodemographic variables. Method: Numerator data, a count of children with PNN‐CP confirmed at 5 years of age ( n = 523), was drawn from two Australian state CP registers (birth years 1973–2012). Poisson regression was used to investigate temporal trends in the prevalence of PNN‐CP by 5‐year intervals, calculated per 10 000 live births. Using data from all state and territory Australian CP registers ( n = 469), distributions of clinical characteristics, PNN‐CP causes, and sociodemographic factors were tabulated (birth years 1995–2012). χ 2 and logistic regression analyses were used to assess associations between sociodemographic profile, Australian reference data, and known causes. Results: A significant temporal decline in PNN‐CP in Victoria ( p = 0.047) and Western Australia ( p = 0.033) was observed. The most common proximal causes of PNN‐CP were cerebrovascular accidents (34%, n = 158), infection (25%, n = 117), and non‐accidental injuries (12%, n = 58). Children born to teenage mothers, Aboriginal and/or Torres Strait Islander mothers, or children born in remote areas were over‐represented in this cohort compared with reference data (all p ≤ 0.001). Infectious causes were strongly associated with teenage motherhood (odds ratio 3.0 [95% confidence interval 1.1–8.2], p = 0.028) and remote living (odds ratio 4.5 [95% confidence interval 2.0–10.2], p < 0.001). Interpretation: Although prevalence of PNN‐CP has declined, the over‐representation of priority populations, and the relative severity of a condition that is largely preventable, suggest the need for more specific primary preventive measures and support. What this paper adds: Prevalence of post‐neonatally acquired (PNN) cerebral palsy (CP) in Australia significantly declined between 1973 and 2012. Cerebrovascular accidents are the most common proximal cause of PNN‐CP. Children born in remote areas are at greater risk of PNN‐CP. What this paper adds: Prevalence of post‐neonatally acquired (PNN) cerebral palsy (CP) in Australia significantly declined between 1973 and 2012. Cerebrovascular accidents are the most common proximal cause of PNN‐CP. Children born in remote areas are at greater risk of PNN‐CP. This original article is commented on by Durkin on pages 13–14 of this issue. Video Podcast: https://youtu.be/vzgiD8bfImc